Imaging of sleep disorders in pre-Parkinsonian syndromes. Issue 4 (5th August 2022) - Ota, Yoshiaki; Kanel, Prabesh; Bohnen, Nicolaas
Abstract : Purpose of review: Neuroimaging has been advanced in the last years and enabled clinicians to evaluate sleep disorders, especially isolated rapid eye movement sleep disorder (iRBD), which can be seen in alpha-synucleinopathies. iRBD is the best prodromal clinical marker for phenoconversion to these neurodegenerative diseases. This review aims to provide an update on advanced neuroimaging biomarkers in iRBD. Recent findings: Advanced structural MRI techniques, such as diffusion tensor imaging and functional MRI, neuromelanin-sensitive MRI, and scintigraphic neuroimaging such as cholinergic PET, dopamine transporter imaging – single-photon emission computerized tomography, perfusional single-photon emission computerized tomography, and cardiac metaiodobenzylguanidine can provide diagnostic and prognostic imaging biomarkers for iRBD, in isolation and more robustly when combined. Summary: New advanced neuroimaging can provide imaging biomarkers and aid in the appropriate clinical assessment and future therapeutic trials.